Gestiòn financiera y su incidencia en la rentabilidad de la empresa Villacrès, periodo 2017 – 2018 - Navarrete Molineros, Luisa María (2019)
The commercial Villacrès, is located at the exit of the Ventanas canton, its commercial activity is the purchase and sale of grains, usually purchases and sales are contact and its financial movements are up to date with good accounting, which the The objective of this case is to review the financial management and its impact on profitability and thus be able to determine and identify the identifiers are its weak points with the methodology to be identified that a transversal design is oriented because it can define a specific time and place applied to the Describe the results evidenced after the study and explanatory because it is expressed sequentially in the development and results of the work